Procalcitonin Level Differences in Patients with Liver Cirrhosis Without Bacterial Infection - Oska Mesanti; Rino Alvani Gani; Marcellus Simadibrata; Suhendro Suhendro (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Procalcitonin level can increase in patients with liver cirrhosis without bacterial infection. The aim of this study is to identify the role of procalcitonin in patients with liver cirrhosis without bacterial infection.Methods: Cross-sectional study was performed to patients with liver cirrhosis without bacterial infection. In patients, we performed procalcitonin level examination and bacterial infection identification. Further, we analysed them to know the procalcitonin level difference in patients with compensated and decompensated liver cirrhosis without bacterial infection.Results: We obtained 39 patients with liver cirrhosis without bacterial infection, male 61.5% with compensated condition found in 17 patients and decompensated in 22 patients. We found significant difference in the average of procalcitonin level in decompensated patients (0.738ng/mL ± 1.185) compared to compensated (0.065ng/mL ± 0.022).Conclusion: Procalcitonin level increased in patients with liver cirrhosis without bacterial infection. The level in decompensated patients were higher compared to compensated patients.